Prognostic Factors Predicting Bleeding After Discharge Requiring Readmission After Thulium Laser Enucleation of the Prostate (ThuLEP) - Davide Perri; Andrea Pacchetti; Elena Morini; Umberto Besana; Giovanni Saredi; Antonio Luigi Pastore; Maria Chiara Sighinolfi; Bernardo Rocco; Salvatore Micali; Federica Mazzoleni; Carlo Buizza; Javier Romero-Rotero; et al. (Société Internationale d’Urologie Journal, 2023)
ObjectivesPostoperative haematuria is a feared complication following prostate enucleation, and it may occur even weeks after discharge. We evaluated the risk of bleeding after discharge and its predictive factors in patients who underwent Thulium laser enucleation of the prostate (ThuLEP). MethodsBetween January 2015 and December 2018, patients with surgical indication for benign prostatic hyperplasia underwent ThuLEP in 4 urology departments. All procedures were performed by experienced urologists. Postoperative haematuria was defined as macroscopic haematuria occurring 7 days after discharge. Readmission rate due to macroscopic haematuria was assessed. Logistic regression models tested for predictors of postoperative bleeding requiring readmission. ResultsOverall, 748 patients were included, and 52 (6.9%) of them were readmitted after discharge because of macroscopic haematuria. No cases of deep venous thrombosis or pulmonary embolism were diagnosed. Mean length of stay for surgical treatment was 2.1 days, and mean hospitalization for readmission was 5.6 days. None of the readmitted patients required reintervention, while 46.1% of them required blood transfusions. Diabetes mellitus (P < 0.05), a long bridge of oral anticoagulant drugs with low molecular weight heparin (LMWH) (P < 0.05) and history of constipation (P < 0.05) were significant predictors of readmission after discharge due to macroscopic haematuria. ConclusionsPatients with a clinical history of diabetes mellitus or constipation and patients who undergo a long bridge of oral anticoagulant therapy with LMWH are at higher risk of bleeding requiring readmission after ThuLEP.